2001
DOI: 10.1159/000053913
|View full text |Cite
|
Sign up to set email alerts
|

A Fetal Wolff-Parkinson-White Syndrome Diagnosed Prenatally by Magnetocardiography

Abstract: We report a case of fetal Wolff-Parkinson-White (WPW) syndrome diagnosed prenatally by magnetocardiography (MCG). At 32 weeks’ gestation, the fetus was diagnosed to have a paroxysmal supraventricular tachycardia by ultrasonography and direct fetal electrocardiogram (ECG). Transplacental fetal therapy by maternal oral administration of propranolol resolved the fetal tachyarrhythmia. Although the wave forms of the fetal MCG at 32 weeks’ gestation were normal, the fetal MCG at 35 weeks’ gestation showed a short P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…3 To date, numerous studies have used FMCG to analyze fetal arrhythmias. 6,8,9,19,20,21 Although analyses of heart rate variability have been attempted on fetal autonomic nervous system functions using FMCG, little has been established using this technique. 22,23 LF and HF bands have been defined according to adult standard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 To date, numerous studies have used FMCG to analyze fetal arrhythmias. 6,8,9,19,20,21 Although analyses of heart rate variability have been attempted on fetal autonomic nervous system functions using FMCG, little has been established using this technique. 22,23 LF and HF bands have been defined according to adult standard.…”
Section: Discussionmentioning
confidence: 99%
“…Recent applications of fetal MCG (FMCG) have yielded details of acquired QT prolongation syndrome, supraventricular tachycardia, and various fetal arrhythmias. [2][3][4][5][6][7][8][9] Attention has recently focused on spectral analysis of heart rate variability as a method for evaluating fetal well-being; for example, the effi cacy of analyses of the coeffi cient of R-R interval variability (CV RR ), and frequency domain values (low-frequency (LF)/high-frequency (HF) ratio). The LF/HF ratio in a supine resting posture has been suggested for the evaluation of autonomic nervous system (ANS) activities.…”
Section: Introductionmentioning
confidence: 99%
“…The successful prenatal diagnosis of SVT and WolffParkinson-White (WPW) syndrome using MCG has been reported recently [5,11]. The accumulation of prenatal diagnosis of fetal SVT and fetal AF indicates that FMCG enables differential diagnosis between SVT and AF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prenatal diagnoses by MCG of a variety of fetal arrhythmias such as complete AV block [6,7], extrasystoles [4], paroxysmal supraventricular tachycardia and Wolff-Parkinson-White syndrome [5] and long QT syndrome [8], have been reported. In the present study, MCG was useful for the prenatal diagnosis of fetal atrial flutter.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors including us have recently reported prenatal diagnosis of fetal arrhythmia such as paroxysmal supraventricular tachycardia and Wolff-Parkinson-White syndrome [5], complete atrioventricular block [6,7], long QT syndrome [8] and extrasystoles [4]. However, to our knowledge no prenatal diagnosis of fetal atrial flutter by MCG has been reported.…”
Section: Introductionmentioning
confidence: 99%